Pendampingan Hafalan Al-Qur’an Pada Anak Di Majlis Ta’lim Al-Baeturrohmah Desa Pasirangin Kecamatan Darangdan - Febi, Febi Angraeni; Rika Purnamasari; Arif Maulana (Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2024)
Abstract: This article aims to provide motivation in improving the development of memorizing short letters through a program to assist children in reciting the Koran in Pasirangin Village RT 05/04, Darangdan District, Purwakarta Regency. This research was carried out from February 12 to February 28 2024. Carrying out this service began with observing the children reciting the recitation during the recitation. The problems faced are memorization which barely progresses every week and reading the Al-Qur'an which is still mispronounced. Therefore, assistance in memorizing letters during recitation will be a solution in improving the development of memorization and reading letters in recitation children at RT 05 RW 04. This research uses the Participatory Action Research (PAR) method. The results of this service show that children's memorization abilities increase after being accompanied by the service team.